PERILAKU BELAJAR SISWA SMP NEGERI 4 RIMBA MELINTANG DALAM PROSES PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI DESA KARYA KABUPATEN ROKAN HILIR - Wulandari, Resti; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research was conducted in Karya Mukti Village, Rimba Melintang District, Rokan Hilir Regency with the aim of knowing children's learning behavior in the online learning process during the pandemic COVID-19 in Karya Mukti Village, Rimba Melintang District, Rokan Hilir Regency and to find out how the attitudes of parents in dealing with children's learning behavior in online learning process during the pandemic COVID-19. This study uses a qualitative qualitative research method with a descriptive approach. Data collection in this study used interview, observation, and documentation techniques. The results of this study are that children's learning behavior in the online learning process during the pandemic COVID-19 has changes in learning, but in the field of achievement many are still able to win in class, meaning that during the pandemic COVID-19, children's learning behavior is still of reasonableness or safe. The attitude of parents in dealing with children's learning behavior during the pandemic COVID-19 plays an important role in providing support for their children while studying. In this case, online learning does not completely have a negative impact on children's learning behavior during a pandemic COVID-19.